Interpersonal forgiveness: validation of the Enright Forgiveness Inventory (EFI-30) in the Spanish sample - Kasprzak, Agata; Martinez-Diaz, Pilar; Molinero Caparrós, Clara; Enright, Roberth (Anales de Psicología / Annals of Psychology, 2023)
Background: Numerous studies have demonstrated the importance of interpersonal forgiveness after a specific offense for improving the health and well-being of individuals. Despite its importance, there is an evident lack of forgiveness evaluation instruments adapted to the Spanish context. The Enright Forgiveness Inventory (EFI-30) is the questionnaire that implements one of the most established and recognized theoretical models in the area of forgiveness. The aim of the present study is to adapt the EFI-30 for the Spanish population and evaluate its psychometric properties. Method: A sample of 426 undergraduate and graduate students (98 men, 328 women) aged from 18 to 30 years (M = 21.24; SD = 2.91), completed the EFI-30 after its adaptation to the Spanish context, as well as the Transgression Related Interpersonal Motivations Inventory (TRIM-18), the Remedial Strategies Scale (RSS) and the Depression Anxiety and Stress Scale (DASS-21). Results: The Confirmatory Factor Analysis showed a good fit to the original six-factor structure (CFI = .91, TLI = .90, IFI = .91, RMSEA = .067). The reliability of these subscales and the instrument was similar to the original version. The results showed adequate criteria and convergent validity. Conclusions: The EFI-30 shows adequate psychometric properties within the Spanish context and is an appropriate instrument for evaluating interpersonal forgiveness of a specific offense in research and clinical intervention.